Late-life depressive symptomatology, motoric cognitive risk syndrome, and incident dementia: the "Nuage" study results - Beauchet, Olivier (2022)
Background: Late-life depressive symptomatology and motoric cognitive risk syndrome (MCR) have independently been associated with an increased risk for incident dementia. This study aimed to examine the association of late-life depressive symptomatology, MCR, and their combination on incident dementia in community-dwelling older adults living in Quebec (Canada). Methods: The study was carried out in a subset of 1,098 community dwellers aged ≥65 years recruited in the "Nutrition as a determinant of successful aging: The Quebec longitudinal study" (NuAge), an observational prospective cohort study with 3 years follow-up. At baseline, MCR was defined by the association of subjective cognitive complaint with slow walking speed, and late-life depressive symptomatology with a 30-item Geriatric Depression Scale (GDS) score >5/30. Incident dementia, defined as a Modified Mini-Mental State score ≤79/100 test and Instrumental Activity Daily Living score <4/4, was assessed at each annual visit. Results: The prevalence of late-life depressive symptomatology only was 31.1%, of MCR only 1.8%, and the combination of late-life depressive symptomatology and MCR 2.4%. The combination of late-life depressive symptomatology and MCR at baseline was associated with significant overall incident dementia (odds ratio (OR) = 2.31 with P ≤ 0.001) but not for MCR only (OR = 3.75 with P = 0.186) or late-life depressive symptomatology only (OR = 1.29 with P = 0.276). Conclusions: The combination of late-life depressive symptomatology and MCR is associated with incident dementia in older community dwellers. The results suggested an interplay between late-life depressive symptomatology and MCR exposing them to an increased risk for dementia.